(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
An experiment was conducted in the wooden canopy affiliated to the Technical College AL-Musaib during the period from the beginning of March until the end of December, 2017 on local lemon citron seedlings aged seven months and grafted on the two seed roots Sour orange and Sweet lemon to study the effect spray and soil fertilizers feeding of organic TARASOIL CALCIO with concentration(0, 50, 100)ml.L-1and sprays of DECSON with concentration of (0, 10, 20) ml. L-1to study the characteristics of vegetative, The soil fertilization in 11/4/2017, 11/5/2017, 11/9/2017 and 11/10/2017, foliar spray in 74//2017, 7/5/2017, 7/9/2017 and 7/10/2017, the experiment was applied by Completely Randomized Design(C.R.D)as factorial experiment(2×3×3) with three replicates and three seedling and 162 seedlings as a total group, The results were analyzed using the statistical analysis program(Excel). The averages were compared according to the least significant difference(L.S.D)at a probability level of (0.05), The type of rootstock have a significant effect on vegetative, The rootstock of sweet lemon increased plant height, leaves the number, leaf area, while rootstock sour orange increased in the stem, Scion. Stalk of sweet lemon +100ml.L-1TARASOIL CALCIO had a suppressive effect in plant height, leaves number while rootstock sour orange suppressive in stock stem, Scion, leaf area, Stalk of sweet lemon +20 ml.L-1 DECSON had a suppressive effect in plant height, leaf number, leaf area while Sour crease stalk a suppressive in main stem, Scion. sweet lemon stalk+100ml.L-1TARASOIL CALCIO+20 ml.L-1 DECSON had a suppressed in plant height, Scion, leaf number, leaf area, while stalk the orange had a suppressive effect in a stock stem.